Proceedings of the Proceedings of the 2nd International Conference on Advance and Scientific Innovation, ICASI 2019, 18 July, B 2019
DOI: 10.4108/eai.18-7-2019.2288544
|View full text |Cite
|
Sign up to set email alerts
|

Proposed ELR Model for E-Learning Readiness Evaluation Based on McKensey 7S Framework

Abstract: One of the utilization of ICT in education including higher education is known as electronic learning (e-learning). E-learning can be interpreted as the delivery of learning content or learning experiences electronically based multimedia computer. Utilization of e-learning well can improve learning outcomes optimally. Lots of advantages e-learning utilization but the failure in the implementation of e-learning is still common despite being supported with large funds and preparation. One of the causes of elearn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…This study found that participants who use e-learning are happy to be considered as part of improving their professionalism. The readiness of teachers to use technology, psychological readiness, sociological readiness, adoption of innovation, ability to create content, and organizational culture are things that can affect the success of e-learning implementation (Maulana & Padang, 2021;Napitupulu et al, 2019;Samba et al, 2020). In addition, the success of e-learning implementation is influenced by students' readiness to use technology, psychological readiness, and adoption of innovation (Alqahtani & Rajkhan, 2020;Ariesta, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that participants who use e-learning are happy to be considered as part of improving their professionalism. The readiness of teachers to use technology, psychological readiness, sociological readiness, adoption of innovation, ability to create content, and organizational culture are things that can affect the success of e-learning implementation (Maulana & Padang, 2021;Napitupulu et al, 2019;Samba et al, 2020). In addition, the success of e-learning implementation is influenced by students' readiness to use technology, psychological readiness, and adoption of innovation (Alqahtani & Rajkhan, 2020;Ariesta, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…E-learning is the electronic delivery of learning content or learning experiences using computers and computer-assisted media (Ahdan et al, 2020;Ellianawati et al, 2021). E-learning can be said as an education system (an educational and learning process) that uses internet media and computer networks to provide teaching materials to students and improve their knowledge and skills (Alqahtani & Rajkhan, 2020;Napitupulu et al, 2019;Samba et al, 2020). Several factors influence the success or failure of eLearning.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Implementasi dari e-learning membutuhkan kesiapan baik dari infrastruktur serta budaya dari institusi. [10]. Kesiapan ini dikenal sebagai E-learning Readiness (ELR).…”
Section: Pendahuluanunclassified
“…Many important components, such as computers and electricity, are not owned, and skills are limited. In addition, the active and participative students required for interactive learning are also rare in developing countries [14] [17].…”
Section: Introductionmentioning
confidence: 99%